Core vocabulary lists for young children and considerations for early language development: a narrative review. (2nd January 2020) - Laubscher, Emily; Light, Janice
Abstract: For early symbolic communicators, acquisition of an initial vocabulary is a critically important achievement that sets the stage for future language development. Children who require augmentative and alternative communication (AAC) rely on others to select and provide these important first words for them. One resource to help guide this process includes published lists of words that may contribute to a core vocabulary for individuals who require AAC. Although some clinicians report that they consider or prioritize core words during the vocabulary selection process, it is not known whether an emphasis on core words will best meet the expressive vocabulary needs of early symbolic communicators. The purposes of this narrative review were to (a) review studies that have developed word lists to inform selection of a core vocabulary for young children who require AAC, (b) compare the words on these lists to the early words used by children with typical development, and (c) consider the implications for vocabulary selection and language development for early symbolic communicators who require AAC. Results suggest that core word lists may under-emphasize many of the types of words that predominate in early expressive vocabulary; these lists may not be the most appropriate resources to guide AAC system design and instruction for early symbolic communicators.